Polisakarida Mengandung Mannan dari Bungkil Inti Sawit Sebagai Antimikroba Salmonella typhimurium pada Ayam - L A Sofyan; N Ramli; K G Wiryawan; K Zarkasie; W G Piliang (Faculty of Animal Science, Bogor Agricultural University, 2007)
Mannan containing polysaccharides could be used as an alternative to replace antibiotics due to their capacity to block the colonization of pathogenic bacteria in the intestine of poultry. The aim of this study was to investigate mannan containing polysaccharides from palm kernel meal (PKM) and its inhibitory effect against Salmonella typhimurium. Hot water extractions were used to isolate mannan containing polysaccharides from cell wall of PKM. In vivo studies were conducted using broiler and layer chicks that were challenged orally with 104 cfu Salmonella typhimurium on third day. Split plot design was used as experimental design with strain as main plot and level of mannan polysaccharides as sub plot. The levels of mannan containing polysaccharides that were used consisted of 0 (R0); 1000 (R1); 2000 (R2); 3000 (R3); 4000 (R4) ppm, in term of total sugar. The results indicated that compared to the control group, feeding PKM containing mannan 4000 ppm decreased (P < 0.01) Salmonella typhimurium incidence. The addition of mannan did not affect feed consumption. On the contrary, the addition of 4000 ppm mannan gave significantly higher feed/weight gain ratio of the chicks (P < 0.05). The administration of feed supplemented with mannan from PKM did not influence weight gain of poultry. It is concluded that mannan from PKM can prevent the colonization of Salmonella typhimurium in poultry. Key words: palm kernel meal, mannan, Salmonella typhimurium, performance, poultry